Specific Aspects of The Use of UAVS By the Employees of The Interior Affairs - Mansur Mirkomilovich Magrubov (Genius Journals, 2025)
The legal basis of the use of drones by the internal affairs body in our country and some problems encountered in their use.
Keywords: unmanned aerial vehicles; drone; monitoring